Memorizing Alfiyah as a Wedding Dowry fromthe Perspective of Maqashid Sharia - Khotim, Ahmad (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The dowry changes according to social, cultural, and economic conditions. The use of Alfiyah memorization as part of the dowry can have a deeper meaning within the maqashid sharia framework. Aim. This study examines the concept of memorizing Alfiyah as a marriage dowry in maqashid sharia and its implementation. Methods. This literature review qualitatively attempts to understand social problems (dowry) holistically which are formed through detailed grammar. Library source data are analyzed qualitatively with the process of data reduction, data presentation, and drawing conclusions or verification. Results. Dowry in Islamic law is a gift from a man to a woman as part of the marriage process. Dowry has a deeper meaning than just material value. The type of dowry depends on the form, value, or characteristics of the gift. The memorization of Alfiyah as a dowry in the concept of Maqashid Syariah can be seen from its objectives, namely Hifz al-Din, Hifz al-Nafs, Hifz al-Aql, Hifz al-Nasl, and Hifz al-Mal. The implications of memorizing Alfiyah as a dowry can have different impacts depending on the cultural context, religion, and social views of the community.